A Constructivist Conception of Legal Norms - Redondo, Maria Cristina (2013)
In this paper I analyze Bulygin’s conception of those legal statements asserting that a certain action is legally obligatory, prohibited or permitted. According to Bulygin these statements are ambiguous. On the one hand, they can affirm the existence or validity of a legal norm in a descriptive sense. In this case they are external statements expressing empirical propositions. On the other hand, they can assert the existence or validity of a norm in an absolute or moral sense, in which case, they are internal (neither true nor false) statements that express a norm or a moral attitude towards it. In the paper I attempt to defend that for a positivist theory, if law is conceived as a set of norms, statements asserting that a certain action is legally permitted or prohibited do not report an empirical fact but do not report the moral or absolute validity of a norm either. They surely assert a normative fact: the legal existence or validity of a normative entity. Nevertheless, this sense of existence or validity depend on human behavior and is relative to a given time and place. I take into account four considerations presented by Bulygin in support of his rejection of this kind of statements expressing internal, normative proposition. In my view, Bulygin’s rejection is fundamentally due to his strict conception of what it means to assume an internal point of view but, even more, it is due to the admission of a false dichotomy between two ways in which an entity can exist: one empirical (relative), the other normative (absolute). In order to criticize this apparent dichotomy, I briefly sketch a constructivist conception in which we can say that legal norms exist. If my reasoning is correct, this conception is one that a positivist legal theory can offer in order to explain internal statements expressing normative facts or propositions.